“To swallow anything”: the close of Fray Gerundio in 1840 - Garrido Muro, Luis (Historia y Comunicación Social, 2016)
Founded in april 1837 by Modesto Lafuente, Fray Gerundio was the main satirical newspaper of its time, as well as one of the most popular and sold. As a result of its constant criticism to power, it received many warnings from the different Governments, the last of which ended up with the close of the newspaper despite the fact it was against the law. The closure made it even more popular and Lafuente became a press freedom champion.
Keywords: Fray Gerundio; Modesto Lafuente; close; 1840